YF Reduces Alveolar Epithelial Cell Apoptosis and PF by Inactivating JAK2/STAT3 - Xiao, Na; Dong, Rui; Dong, Ying; Li, Xiaoli; Wang, Yuhui; Zhang, Shusen; Zhou, Xianmei (Current Pharmaceutical Design, 2025)
<span class=
Keywords: vimentin